1984
DOI: 10.1038/bjc.1984.117
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and heat sensitivity of cells from two slowly growing human melanoma xenografts

Abstract: Summary The radiation and heat sensitivity of cells from two melanin-rich, slowly growing human melanoma xenografts (B.E. and R.A.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Breast cancer is a relatively radiosensitive tumor and, in general, may be more radiosensitive than NSCLC. 20,21 Therefore, it is not surprising that breast cancers of a few centimeters were controlled by our high-dose irradiation method. Even when the tumor develops local recurrence, salvage surgery may be feasible; indeed, one of our patients underwent salvage breast-conserving surgery successfully.…”
Section: Discussionmentioning
confidence: 97%
“…Breast cancer is a relatively radiosensitive tumor and, in general, may be more radiosensitive than NSCLC. 20,21 Therefore, it is not surprising that breast cancers of a few centimeters were controlled by our high-dose irradiation method. Even when the tumor develops local recurrence, salvage surgery may be feasible; indeed, one of our patients underwent salvage breast-conserving surgery successfully.…”
Section: Discussionmentioning
confidence: 97%
“…Light and electron-microscopic examinations showed that the histological appearance of the xenografts in these passages was similar to that of the metastases from which they were derived. The growth characteristics of subcutaneous flank tumours of the xenografts, approximately 200 mm3 in size, have been reported previously Rofstad, Wahl & Brustad, 1984).…”
Section: Xenograftsmentioning
confidence: 67%